PENGARUH PEMANGKASAN TANAMAN LADA DAN TAJARNYA TERHADAP HASIL - USMAN DARAS; PASRIL WAHID (Pusat Penelitian dan Pengembangan Perkebunan, 2000)
The effect of living post and pepper vines primings on the pepper yieldTo obtain good yield of pepper, farmers fequently apply various treatments to their crops, including pruning of the pepper vines and or their living post. Studies on the aspects of the pruning ae however very limited. Therefore a ield experiment was conducted to investigate the effects of pruning of pepper vines and their living post on the pepper yield. The experiment was carried out at Sukamulya Research Station, Sukabumi. A split plot design with three rcplicaties was used. The main plot was the pruning of living post, and the sub plot was the pruning of pepper vines Plot size was 20 plants per plol wilh spacing of 2.5 m x 2.5 m Results showed that there was signiicant interaction between the pruning of living post and pepper vines. The pruning of living post may be carried out either 3 times (October, January and April) or twice (October and January) a year. However. If the pruning of the living post is carried out 3 times per year, Ihe vine would be pruned once a year or not at all. On the other hand, if the pruning of living post is carried out twice a year, the pepper vines would be pruned 6 times a year.